Hospital Acquired Pathogenic Escherichia coli from Clinical and Hospital Water Samples of Quetta Balochistan. (13th October 2022) - Akbar, Ali; Naeem, Wajeeha; Liaqat, Faiza; Sadiq, Muhammad Bilal; Shafee, Muhammad; Gul, Zareen; Khan, Shabir Ahmad; Mengal, Hasina; Chein, Su Hlaing; Qasim, Sadia; Arshad, Muhammad; Rehman, Fazal Ur; et al.
Abstract : A study was conducted to determine the prevalence and drug resistance of Escherichia coli present in urinary tract infected patients and hospital drinking water. A total of eighty urine samples from clinically suspected patients and thirty tap water samples from hospital vicinity were collected and analyzed for the presence of E. coli . The isolates were preliminary identified based on morphological characteristics, biochemical test and further confirmed by polymerase chain reaction (PCR) using uidA primer. Isolates were subjected to antibiogram studies and analyzed for the presence of drug resistance ( ESBL blaCTX-M-15, tetA, and TMP-SMX dfrA1 ) and pathogenicity associated pyelonephritis-associated pili ( PAP ) and Heat-labile (LT) toxin genes. Urine samples 19/80 (23.75%) and water samples 8/30 (26.7%) were found contaminated with E. coli . It was found that 12/19 (63%) bacterial isolates were extended spectrum beta-lactamase (ESBL) producers in clinical and 6/8 (75%) in water isolates whereas tetracycline resistance in clinical and water isolates was 11/19 (58%) and 6/8 (75%), respectively. The trimethoprim resistance gene was confirmed in 12/19 (63%) in clinical and 2/8 (25%) in water isolates. All the clinical and water isolates were found carrying pili PAP gene. It was concluded that the presence of drug resistant and pathogenic E. coli in clinical and water samples is extremely alarming for public health due to cross contamination and bacterial transfer from clinical samples to water and vice versa.